Risk of Needle Stick Injuries among Night Shift Nurses in a Selected Private and Government Hospital in Accra: A Case of the Trust Hospital Limited and the Ridge Regional Hospital. - Ampomah, A.F. (University of Ghana, 2016)
Background: The nature of the work of a nurse, requires a high level of alertness and vigilance in order to avoid certain preventable errors and injuries such as needle stick injuries (NSIs). Night shifts, being a common practice among nurses work schedules, conflicts with biological patterns and is further linked to fatigue and sleep during working hours at night. Subsequently this affects their level of performance and increases the rate of injuries and accidents. Objectives: This study assessed the prevalence of NSIs among nurses working on night shift, the factors that influence the occurrence of NSIs among night shift nurses (NSNs) as well as the association between night shift work and needle stick injuries. Methods: A simple random cross-sectional study was conducted among a total of 204 NSNs in the Trust and Ridge hospitals in Accra. Data was from obtained from nurses through a semi-structured questionnaire. Statistical analysis of data sets was done using Stata version 13. Percentages, frequencies, odds ratio as well as p-values were used in describing data obtained. Graphical representation of data was done where appropriate using tables, pie charts, bar charts. Chi-square test was used to test for association between night shift work and NSIs. The factors that influenced the risk of NSIs occurring were determined using a multivariate logistic regression. Odds ratios at a 95% level of confidence were used to explain the level of risk of occurrence of NSIs among NSNs. Level of significance was set at p < 0.05. Results: The study findings revealed a low prevalence of NSIs among NSNs of both the Trust (25%) and Ridge (26.7) hospitals in Accra. Factors such as age, sex, years of practice, needle usage, blood withdrawal, needle recapping, work environment, rushing on the job as well as fatigue were found to have a likelihood of influencing the occurrence of NSIs among NSNs. No association was found between night shift work and the occurrence of NSI among the NSNs. Conclusion: Results of this study showed low prevalence of NSIs among NSNs at the both Trust and Ridge Regional hospitals.
Thesis(MSc)-University of Ghana, 2016
Keywords: Needle Stick Injuries; Night Shift Nurses; Trust Hospital Limited; Ridge Regional Hospital